OP0010 Autologous Hematopoietic Stem Cell Transplantation Increases T-Cell PD-1 Expression and Regulatory Mechanisms in Systemic Sclerosis Patients. (9th June 2015) - Arruda, L.C.M.; Oliveira, M.C.; Moraes, D.A.; Covas, D.T.; Malmegrim, K.C.R.
Abstract : Background: Autologous Hematopoietic Stem Cell Transplantation (AHSCT) has been proved as an alternative for the treatment of severe and progressive systemic sclerosis (SSc) patients [1]. To understand the therapeutic mechanisms enrolled in AHSCT and to further improve its efficacy, we aimed to evaluate the post-transplantation immune reconstitution [2] Objectives: To evaluate the immune reconstitution after AHSCT through quantification of total, naive and memory CD4 + T-cells, regulatory T-cells and of exhausted T- and B-cells. Methods: Peripheral blood was collected from nine diffuse SSc patients before and at 6, 12, 18 and 24 months post-AHSCT. Peripheral blood mononuclear cells were immunophenotyped by flow cytometry. Results: Total CD3 + CD4 + T-cell counts were significantly decreased ( P <0.01) from 6-24 months post-AHSCT when compared to baseline due intense depletion of CD4 + CD45RO - CD27 + naive and CD4 + CD45RO + CD27 + central-memory cells. No changes were detected in the CD4 + CD45RO - CD27 - effector or in the CD4 + CD45RO + CD27 - effector memory T-cell numbers ( P >0.05). At the same time, higher counts of CD4 + CD25 hi FoxP3 + regulatory T-cells (Tregs) were observed at 12 months post-AHSCT when compared to baseline ( P <0.05), indicating an increasing proportion of Treg/CD3 + CD4 + T-cell ratio from 6 months until the end of follow-up ( P <0.01). Higher expression (%) of CTLA-4 on CD4 + CD25 hi T-cells was observed only at 24 months post-AHSCT ( P <0.05), and increasing GITR expression (%) was observed from 6-24 months ( P <0.05). PD-1 expression (%) increased at 6 and 12 months post-AHSCT in CD3 + CD4 + ( P <0.01) and in CD3 + CD8 + T-cells ( P <0.05) when compared to baseline. No changes were observed in CD19 + B-cells. Conclusions: Our results suggest improvement of peripheral immunoregulatory mechanisms and depletion of central memory CD4 + T-cells after AHSCT, which may contribute to reestablishment of self-tolerance and to control of autoimmunity in SSc patients. References: van Laar JM, Farge D, Sont JK, Naraghi K, Marjanovic Z, Larghero J, et al. Autologous hematopoietic stem cell transplantation vs intravenous pulse cyclophosphamide in diffuse cutaneous systemic sclerosis: a randomized clinical trial. JAMA. 2014 Jun; 311(24):2490-2498. Baraut J, Grigore EI, Jean-Louis F, Khelifa SH, Durand C, Verrecchia F, et al. Peripheral blood regulatory T cells in patients with diffuse systemic sclerosis (SSc) before and after autologous hematopoietic SCT: a pilot study. Bone Marrow Transplant. 2014 Mar; 49(3):349-354. Acknowledgements: Funding was provided by CNPq and by the Sao Paulo Research Foundation (FAPESP). Disclosure of Interest: None declared